Strategic Role Of Sales Promotion In Increasing The Number Of Vermox Drug Sales - Kuswardani, Dyah Corry; Nurhidayati, Nurhidayati; Wibisono, Totok (Economics and Business Solutions Journal, 2018)
This study aims to contribute   to understanding about strategic role of sales promotion in increasing the number of sales of Vermox worm medicine products. The data used in this study is secondary data which includes sponsorship event costs, window displays, loyalty programs, gimmicks, and price discounts. Multiple linear regression analysis tool is used to show the effect of sales promotion costs on total sales. Hypothesis testing results show that there is a significant influence of Event Sponsorship and Discounts on the number of sales. Window displays, Loyalty and Gimmick Programs have no significant effect on the number of sales. The regression equation in this study is Y1 = 0.071X1 - 0.001X2 - 9.563X3 - 0.001X4 + 0.038X5.